2016
DOI: 10.1038/srep39473
|View full text |Cite
|
Sign up to set email alerts
|

Blocking triggering receptor expressed on myeloid cells-1 attenuates lipopolysaccharide-induced acute lung injury via inhibiting NLRP3 inflammasome activation

Abstract: Acute lung injury (ALI) is associated with high mortality and uncontrolled inflammation plays a critical role in ALI. TREM-1 is an amplifier of inflammatory response, and is involved in the pathogenesis of many infectious diseases. NLRP3 inflammasome is a member of NLRs family that contributes to ALI. However, the effect of TREM-1 on NLRP3 inflammasome and ALI is still unknown. This study aimed to determine the effect of TREM-1 modulation on LPS-induced ALI and activation of the NLRP3 inflammasome. We showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 51 publications
2
72
0
Order By: Relevance
“…In the present study, the higher expressions of IL‐1β, IL‐6 and TNF‐α in serum or inflammatory endometrium after LPS treatment suggested an acute inflammatory reaction and potential fibrinogen and cell apoptosis in the uterus. Previous studies reported that inhibition of TREM‐1 suppressed IL‐1β‐induced chondrocyte injury, reduced colitis in mice, alleviated Streptococcus ‐induced syndrome and attenuated LPS‐induced acute lung injury (Liu, et al , ; Kökten, et al , ; Tang and Dong, ; Han, et al , ). Consistent with these results, the lower levels of IL‐1β, IL‐6 and TNF‐α in serum or uteri in the Trem1 −/− mice than in the wild‐type mice after LPS stimulation suggested that the TREM‐1 gene knockout could attenuate LPS‐induced endometritis, probably by inhibiting inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the higher expressions of IL‐1β, IL‐6 and TNF‐α in serum or inflammatory endometrium after LPS treatment suggested an acute inflammatory reaction and potential fibrinogen and cell apoptosis in the uterus. Previous studies reported that inhibition of TREM‐1 suppressed IL‐1β‐induced chondrocyte injury, reduced colitis in mice, alleviated Streptococcus ‐induced syndrome and attenuated LPS‐induced acute lung injury (Liu, et al , ; Kökten, et al , ; Tang and Dong, ; Han, et al , ). Consistent with these results, the lower levels of IL‐1β, IL‐6 and TNF‐α in serum or uteri in the Trem1 −/− mice than in the wild‐type mice after LPS stimulation suggested that the TREM‐1 gene knockout could attenuate LPS‐induced endometritis, probably by inhibiting inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…TNF‐α, IL‐1β, IL‐8 and IL‐6) or to induce the release of myeloperoxidase (MPO) (Bouchon, et al , ). Furthermore, inhibition of TREM‐1 either by antibodies or by gene targeting could protect mice against LPS or live E. coli ‐induced shock or sepsis (Bouchon, et al , ; Liu, et al , ). Additionally, it has been demonstrated that TREM‐1‐Ig Fc fusion protein treatment could lower the serum levels of TNF‐α and IL‐1β after LPS administration (Wang, et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Mild pulmonary edema and infiltration of inflammatory cells was seen in mice from the control and colonization groups directly after aerosol inhalation and disappeared the next day, which we thought was caused by the non-infectious irritation during inhalation. TREM-1 is a receptor that triggers an inflammatory cascade and is highly expressed in neutrophils and monocytes (21). It has been reported that activation of TREM-1 immediately induces rapid degranulation of neutrophilic granules and drives the release of proinflammatory factors, including MIP-1, MCP-1 and IL-8, thus playing an important regulatory role in inflammation (22).…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasome is assembled by NLRP3, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), caspase-1 released after an endogenous ‘‘danger signal” and exogenous infection, comprise an important cytosolic protein complex [34]; this provides a caspase-1-activation platform to promote the maturation and release of proinflammatory cytokines, including IL-1β and IL-18 [35]. NLRP3 inflammasome plays a critical role in lung injury in diverse models [34, 36]. Inhibition of NLRP3 inflammasome activation attenuated lung tissue damage and the pulmonary inflammatory response in a mouse model of LPS-induced lung injury [36].…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasome plays a critical role in lung injury in diverse models [34, 36]. Inhibition of NLRP3 inflammasome activation attenuated lung tissue damage and the pulmonary inflammatory response in a mouse model of LPS-induced lung injury [36]. Inhibition of NLRP3 inflammasome also attenuated ventilation-induced lung injury [34].…”
Section: Discussionmentioning
confidence: 99%